THE ROLE OF MACROSCOPIC TURBULENT DIAMAGNETISM IN ENSURING LONG-TERM STABILITY OF SUNSPOTS - Krivodubskij, V. N. (Одеські астрономічні публікації, 2020)
We investigated the role of macroscopic turbulent diamagnetism in ensuring the long-term stability of the equilibrium state of the sunspots. The physical meaning of macroscopic diamagnetism of turbulent plasma is expulsion of a large-scale magnetic field from areas with increased turbulence intensity to areas with reduced turbulence. We follow the idea of Krause & Rüdiger (1975) that a strong magnetic field of a sunspot modifies the structure of turbulence in spot umbra, so it becomes two-dimensional. In addition, we take into account the strong magnetic suppression of turbulence in the spot, where it becomes less intense than the turbulent convection around the spot. As a result, a relatively thin transitional vertical layer of permeable convection (convective overshot layer) should be formed between these sections, in which the intensity of turbulent pulsations decreases noticeably in the transverse direction during the transition from the convection section to the spot. In this permeable convection layer, the effect of turbulent diamagnetic displacement of the magnetic field from the convection region to the sunspot occurs. Owing to the two-dimensional turbulent diffusion, the magnetic field of the spot spreads outwards, while the intense turbulent pulsations in the convection region return the magnetic field in the opposite direction, back to the spot. Therefore, these two oppositely directed processes of magnetic field transfer in the horizontal plane compete with each other. As a result, the magnetic fields that are transferred due to turbulent diffusion outward from the sunspot will be thrown backward into the spot due to strong external turbulent convection. In our opinion, this effect should ensure long-term stability of the equilibrium state of the magnetic field of sunspots and support them in the form of isolated vertical unipolar magnetic force tubes.